2014
DOI: 10.1371/journal.pgen.1004084
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive tRNA Deletion Library Unravels the Genetic Architecture of the tRNA Pool

Abstract: Deciphering the architecture of the tRNA pool is a prime challenge in translation research, as tRNAs govern the efficiency and accuracy of the process. Towards this challenge, we created a systematic tRNA deletion library in Saccharomyces cerevisiae, aimed at dissecting the specific contribution of each tRNA gene to the tRNA pool and to the cell's fitness. By harnessing this resource, we observed that the majority of tRNA deletions show no appreciable phenotype in rich medium, yet under more challenging condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
85
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(99 citation statements)
references
References 73 publications
(81 reference statements)
14
85
0
Order By: Relevance
“…Further, the expression of the anticodon isoacceptor families, relative to each other, was stable across mammalian development. In yeast, tRNA genes can compensate for changing levels of expression of another member of their isoacceptor family, an effect demonstrated by systematic deletion of tRNA genes (Yona et al 2013;Bloom-Ackermann et al 2014). Our data are a first direct indication that a compensatory mechanism must also operate dynamically in mammals to stabilize the collective expression of a given isoacceptor family.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Further, the expression of the anticodon isoacceptor families, relative to each other, was stable across mammalian development. In yeast, tRNA genes can compensate for changing levels of expression of another member of their isoacceptor family, an effect demonstrated by systematic deletion of tRNA genes (Yona et al 2013;Bloom-Ackermann et al 2014). Our data are a first direct indication that a compensatory mechanism must also operate dynamically in mammals to stabilize the collective expression of a given isoacceptor family.…”
Section: Discussionmentioning
confidence: 62%
“…We did this since prior studies have shown that sequence variation in internal regulatory sequences of tRNA genes have no clear relationship with their expression levels (Oler et al 2010;Canella et al 2012). We searched for regulatory sequence elements acting in cis that could direct the Pol III recruitment to tRNA genes as described previously (Giuliodori et al 2003;Bloom-Ackermann et al 2014). To investigate the differences in Pol III binding for every pair of timepoints, we used MEME (Bailey and Elkan 1994) and TOMTOM (Gupta et al 2007) to search for enrichment of specific motifs in the 500-bp upstream regions of differentially expressed tRNAs, using stably expressed tRNA genes as the background (Supplemental Table 10; Methods).…”
Section: Stable Isoacceptor Anticodon Abundance Through Development Imentioning
confidence: 99%
“…Although a tRNA deletion resource has already been developed and has revealed interesting and distinct cellular responses to the deletion of tRNA families (Bloom-Ackermann et al 2014), it cannot be used for large-scale studies with pooled strains, since the deletion strains are not barcoded. In this respect our collection is a step forward, and will allow comprehensive genome profiling of cellular fitness in different environments (Delneri et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the ratio of cognate versus near-cognate tRNA genes can potentially affect the interference by unmodified tRNAs. 148 Finally, tissue specific RNA expression or different genetic mouse backgrounds can affect the outcome of a phenotype significantly (please refer also to the checklist in Table 4). 149,150 All these factors need to be kept in mind, when modeling RNA modification pathologies, and it is possible that certain defects in humans can be best mimicked by studying inducible pluripotent stem cells (iPSC) and differentiated cells derived from them.…”
Section: Discussionmentioning
confidence: 99%